2019
DOI: 10.1016/j.ajog.2019.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding outcomes after assisted conception

Abstract: gestational ages. Moreover, because the use of an artificial placenta requires catheterization of umbilical vasculature and a system with sufficiently low resistance so as not to compromise the fetal heart, it seems unlikely that fetuses much below 20 weeks gestation could be adapted to or maintained on an artificial placenta. Because, from a functional perspective, current artificial placenta-based systems essentially are limited to gas exchange and the delivery of nutrition and medication, it is not possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Still, this difference was no longer significant after adjusting for plurality and preterm birth. These differences may depend on studies' methodological limitations, which includes inadequate recruitment, lack of appropriate comparison groups and inappropriate adjustment for potential causal intermediates such as preterm birth or multiple births 14 . Indeed, Weng et al in a study conducted in a sample of 3465 women, highlighted that the effects of mode of conception on breastfeeding outcomes became insignificant in cases of exclusive singleton birth comparison 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, this difference was no longer significant after adjusting for plurality and preterm birth. These differences may depend on studies' methodological limitations, which includes inadequate recruitment, lack of appropriate comparison groups and inappropriate adjustment for potential causal intermediates such as preterm birth or multiple births 14 . Indeed, Weng et al in a study conducted in a sample of 3465 women, highlighted that the effects of mode of conception on breastfeeding outcomes became insignificant in cases of exclusive singleton birth comparison 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Literature highlight controversial results about breastfeeding duration after assisted pregnancy, in particular if this association exists or not, and if depends by different types or length of fertility intervention. Some authors demonstrated that women who conceived through ART stopped breastfeeding earlier or breastfed for a shorter period than those who conceived spontaneously; other authors showed no differences in the length of breastfeeding between spontaneous and fertility treated conceiving [8][9][10][11][12][13][14][15][16][17] .…”
mentioning
confidence: 99%